2015
DOI: 10.1016/j.aquaculture.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive factors in microbial biomass have the capacity to offset reductions in the level of protein in the diet of black tiger shrimp, Penaeus monodon

Abstract: A factorial experiment was conducted with black tiger shrimp (Penaeus monodon) juveniles to determine the effects of varying protein inclusion in the diet and also varying inclusion of a microbial biomass on growth, feed and nutrient utilization when fed in indoor laboratory conditions. The growth performance of the shrimp improved with increasing diet protein level. However, in the absence of the added microbial biomass, this growth performance plateaued at the 480. g/kg protein level. The addition of the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
2
18
2
Order By: Relevance
“…One notable outcome of the study was the slower growth of broodstock fed diets containing MB, compared to broodstock fed the control diet, in the grow-out phase. This result is inconsistent with former studies which have reported improved growth of juvenile shrimp when fed diets including MB (Anand et al, 2014;Glencross et al, 2013;Glencross et al, 2014;Glencross et al, 2015). In addition to the possibility that the MB grow-out diet was less optimal for growth than the control grow-out diet, when fed in low-density broodstock ponds during the grow-out phase, there are several other possibilities to explain the differences in results from former studies.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…One notable outcome of the study was the slower growth of broodstock fed diets containing MB, compared to broodstock fed the control diet, in the grow-out phase. This result is inconsistent with former studies which have reported improved growth of juvenile shrimp when fed diets including MB (Anand et al, 2014;Glencross et al, 2013;Glencross et al, 2014;Glencross et al, 2015). In addition to the possibility that the MB grow-out diet was less optimal for growth than the control grow-out diet, when fed in low-density broodstock ponds during the grow-out phase, there are several other possibilities to explain the differences in results from former studies.…”
Section: Discussioncontrasting
confidence: 79%
“…The proximate analysis revealed compositional differences between the MB and control maturation diets, such as the lower protein content of the MB diet. Interestingly, previous works by Glencross et al (2015) have demonstrated the use of MB, and particularly Novacq™, as a clear mechanism for offsetting decreases in performance directly related to reductions in dietary protein levels. However, it must be noted that these assessments were undertaken for juvenile shrimp only (~3 g) and with respects to growth and not reproductive performance.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This result is inconsistent with former studies which have reported improved growth of juvenile shrimp when fed diets including MB , Glencross et al, 2013, Anand et al, 2014, Glencross et al, 2015. There are several factors that may have contributed to the growth rates observed in the present study.…”
Section: However These Results Contrast To the Positive Effects On Rcontrasting
confidence: 57%